Upgrading the physiochemical and sensory quality of yogurt by incorporating polyphenol-enriched citrus pomaces with antioxidant, antimicrobial, and antitumor activities - Alamoudi, Soha A.; Saad, Ahmed M.; Alsubhi, Nouf H.; Alrefaei, Ghadeer I.; Al-Quwaie, Diana A.; Binothman, Najat; Aljadani, Majidah; Alharbi, Mona; Alanazi, Humidah; Babalghith, Ahmad O.; Almuhayawi, Mohammed S.; Gattan, Hattan S.; et al. (Frontiers in Nutrition, 2022)
Industrial pomaces are cheap sources of phenolic compounds and fibers but dumping them in landfills has negative environmental and health consequences. Therefore, valorizing these wastes in the food industry as additives significantly enhances the final product. In this study, the citrus pomaces, orange pomace (OP), mandarin pomace (MP), and lemon pomace (LP) were collected by a juice company and subjected to producing polyphenols and fiber-enriched fractions, which are included in functional yogurt; the pomace powder with different levels (1, 3, and 5%) was homogenized in cooled pasteurized milk with other ingredients (sugar and starter) before processing the yogurt fermentation. The HPLC phenolic profile showed higher phenolic content in OP extract, i.e., gallic acid (1702.65), chlorogenic acid (1256.22), naringenin (6450.57), catechin (1680.65), and propyl gallate (1120.37) ppm with massive increases over MP (1.34-37 times) and LP (1.49-5 times). The OP extract successfully scavenged 87% of DPPH with a relative increase of about 16 and 32% over LP and MP, respectively. Additionally, it inhibits 77-90% of microbial growth at 5-8 µg/mL while killing them in the 9–14 µg/mL range. Furthermore, OP extract successfully reduced 77% of human breast carcinoma. Each of pomace powder sample (OP, MP, LP) was added to yogurt at three levels; 1, 3, and 5%, while the physiochemical, sensorial, and microbial changes were monitored during 21 days of cold storage. OP yogurt had the highest pH and lowest acidity, while LP yogurt recorded the reverse. High fat and total soluble solids (TSS) content are observed in OP yogurt because of the high fiber content in OP. The pH values of all yogurt samples decreased, while acidity, fat, and TSS increased at the end of the storage period. The OP yogurts 1 and 3% scored higher in color, flavor, and structure than other samples. By measuring the microbial load of yogurt samples, the OP (1 and 3%) contributes to the growth of probiotics (Lactobacillus spp) in yogurt samples and reduces harmful microbes. Using citrus pomace as a source of polyphenols and fiber in functional foods is recommended to enhance their physiochemical and sensory quality.